Mechanical and dielectric properties of SEBS modified by graphite inclusion and composite interface. (February 2016) - Grigorescu, Ramona Marina; Ciuprina, Florin; Ghioca, Paul; Ghiurea, Marius; Iancu, Lorena; Spurcaciu, Bogdan; Panaitescu, Denis Mihaela
Abstract: Tough and flexible dielectrics were prepared using graphite (G), a natural and low-cost resource, as filler in polystyrene-b-(ethylene-co-butylene)-b-polystyrene (SEBS) and maleinized SEBS (SEBS-MA) matrices. The disintegration of graphite in submicron particles was accomplished by the shear forces during the melt processing step and it was highlighted by atomic force microscopy. Simultaneous increase of tensile strain, strength and Young's modulus was noticed for SEBS/G and SEBS-MA/G composites compared to unfilled matrices, this remarkable feature being previously reported only for some nanocomposites. Moreover, an exponential variation of the dielectric permittivity with the volume fraction of G was obtained. Higher reinforcing efficiency and better dielectric properties were observed in SEBS-MA/G composites, compared to the corresponding SEBS/G composites, due to the stronger polymer–filler interface and better dispersion of graphite. This study brings new insights into nanolevel properties of SEBS composites and it opens new perspectives on high performance composites by using graphite instead of expensive graphene and efficient melt mixing process. Graphical abstract: Highlights: Tough and flexible dielectrics were prepared using low-cost graphite filler in SEBS. Disintegration of graphite (G) in submicron particles was highlighted by AFM. Simultaneous increase of elongation, strength and modulus was noticed in composites. Exponential variation of the dielectric permittivity with G fraction was obtained. Better mechanical and dielectric properties for SEBS-MA compared to SEBS composites.